Microfinance Model- A Dynamic Drive Towards the Women Empowerment - Patel, Ruchi (European Scientific Journal, ESJ, 2017)
This study is based on the microfinance model which works for poverty reduction and financial inclusion mechanism for development of social systems and livelihood development in developing countries. Women are a powerful force that can be empowered to the benefit of their families, society and nation to which they belong. But in the rural and tribal area of Indian patriotic society, women face discrimination in their family with social, economic and political life. This study has examined the impact of microfinance on women empowerment in the context of various model and initiatives taken by programmes and schemes of government and nongovernment organisations. The methodology of the present study relies on case study method of women Self-Help Group (SHG). Secondary data has been collected from the annual and other reports of different departments and ministries, journals, books, research papers. This study suggest that microfinance played a very important to created financial resources for poor women but it requires investment in capacity building over a period of time, it will help to build the social capital and helps to bring economic prosperity.